Pengaruh Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Kabupaten/ Kota Sumatera Barat - Wyanet Putri Alisha; Yulhendri Yulhendri (Universitas Negeri Padang, 2021)
This study aims to know the effect of economic growth as measured by the real GDP growth rate at constant prices on the level of poverty in the districts / cities of West Sumatra in a period of 10 years, from 2011 to 2020. This study uses secondary data obtained from the publication of the central bureau of statistics. The analysis used in this study used panel data linear regression analysis using a fixed effect model approach. The results of this study indicate that the rate of economic growth has a significant negative effect on poverty levels. This means that increased economic growth can reduce the level of poverty in the regency / cities of West Sumatra.Keywords: poverty, pdrb, economic growth